Sistema informático de gestión documental para los procesos de contratación pública de la Prefectura de Cotopaxi. - Chigue Chicaiza, Alex Jerson (2021)
All public institutions in Ecuador must make their acquisition of goods and services through the Official Public Procurement System, according to this, it can be mentioned that the Prefecture of Cotopaxi carries out a set of processes continuously, so that a public procurement project will be viable or not, among these processes it is said that it begins with the development of a project profile, need report, electronic catalog verification, market study, terms of reference, process start report, among other elements which in order to have legal validity they must be electronically signed by obligation as regulated by the Organic Law of the National Public Procurement System. That is why a computer system is proposed that is capable of managing the development of all documents associated with the contracting of goods and services at the Prefecture of Cotopaxi, incorporating digital signature certificates in the way that the documentation which flows within the respective system has legal validity in accordance with what requested is by the National Public Procurement Service of Ecuador. Likewise, the proposed system will become a repository of information which is required in the public institutions where it is essential to keep the data for a long time because of the fact that the General State Comptroller may request an audit at any time and it is the time where the institution must have backups of all the documentation associated with the purchases made by the Prefecture of Cotopaxi.